Cluster-Based Local Economic Development (The Case of Cluster Development In Umbul Ponggok, Klaten) - Nunuk Dwi Retnandari; David Merauje (Indonesian Association for Public Administration (IAPA), 2018)
Local economic development is one of the means regional governments frequently employ to improve community welfare. However, improper management and development patterns would lead to failure in the implementation of economic development or outside communities may enjoy the benefits of economic development instead. Umbul Ponggok is a community-based tourist destination and it has, to this day, been capable of becoming a source of livelihood for most of the residents living in the area. The community’s involvement at every level of the decision making process and implementation guarantees continuity in the local economy they develop. Additionally, the transparent and accountable management in place ensures the high level of trust people have. Such superior level of trust and involvement was no overnight feat, persistence and wholeheartedness of initiators along with the support of various parties (university, banking institutions, NGO, and others) made certain that the numerous issues encountered were resolved, all challenges overcome, and every opportunity taken.